ANALISIS SIKAP MAHASISWA KETIKA BERKOMUNIKASI KEPADA DOSEN PEMBIMBING - Jannah, Balqis Nurul; Pasyah, Kamila; Kusumah, Habima Perdana; Simanjuntak, Rafly Ramadhan (Journal of Community Devation, 2025)
This study aims to analyze students' attitudes in communicating with supervisors, as well as the factors that influence these attitudes. Effective communication between students and supervisors is very important in supporting the smooth running of the academic guidance process, which ultimately contributes to the achievement of educational goals. Through a qualitative approach, this study identified that students' attitudes are influenced by psychological factors, social norms, academic experiences, and the communication media used. These findings indicate that an open, proactive, and respectful attitude from students can improve the quality of interactions with supervisors. This study also provides recommendations for students to further develop their communication skills, and for lecturers to create an environment that supports constructive communication.